Is There a Role for Higher Education Institutions in Improving the Quality of First Employment? - Seamus McGuinness; Adele Whelan; Adele Bergin (Institute for the Study of Labor (IZA), 2016)
This paper examines the potential role of higher education institutions in reducing labour market mismatch amongst new graduates. The research suggests that increasing the practical aspects of degree programmes, irrespective of the field of study, will reduce the incidence of initial mismatch. In terms of routes into the labour market, higher education work placements with the potential to develop into permanent posts and the provision of higher education job placement assistance were found to have substantial impacts in reducing the incidence of graduate mismatch. The use of private employment agencies was found to significantly heighten the risk of subsequent mismatch.
Keywords: J24; J31; 330; graduate labour market; overeducation; over-skilling; recruitment; course composition